Gladiators deadly arena sports of ancient Rome - Epplett, Christopher (Skyhorse Publishing, 2016)
A history of gladiators--with an added bite! The Gladiators is a comprehensive survey of arena sports in ancient Rome, focusing upon gladiatorial combat and the beast-hunts (venationes). While numerous books have been written on arena spectacles in ancient Rome, they generally neglect the venationes, despite the fact that the beast-hunts, in which men were pitted in mortal combat against various dangerous wild animals (including lions, tigers, elephants, and rhinos), were almost as popular as gladiatorial spectacles and were staged over a longer period of time. Dr Christopher Epplett, gives a full and detailed treatment of both types of spectacle. The author starts by explaining the origins of these bloody combat sports in the late Roman Republic, before surveying the growth of these events during the first two centuries of the Empire, when emperors possessed the resources to stage arena spectacles on an unmatched scale. The details of the training, equipment, and fighting styles used by different types of combatants are covered, as are the infrastructure of the arenas and behind-the-scenes organization that was essential to the successful staging of arena events. Particular attention is paid to the means by which Roman spectacle organizers were able to procure the countless wild animals necessary for the staging of venationes throughout the Empire. A gladiator book with added bite, The Gladiators is sure to be welcomed by scholars and general readers alike